PRODUKSI JAGUNG PAKAN NK 212 PADA LAHAN KERING DENGAN BERBAGAI DOSIS PUPUK KANDANG - Indriani indriani; Rika Hari Lestari; Reski Amaliah; Nursani Nursani; Dewi Ramadhani; Ristasari Sadi (Jurnal Agriovet, 2025)
Hybrid corn NK 212 is part of the agricultural commodities that have an important function in supporting the activities of the livestock industry in Indonesia because corn grains can be used as poultry feed and corn straw can be used as feed for ruminants. This study was arranged based on a Randomized Block Design (RAK) with 4 treatments and 6 replications. Treatment K0 = control, K1 = 1 kg, K2 = 2 kg, K3 = 3 kg. Analysis of variance showed that the application of manure with different doses showed a very significant effect (P <0.01) on seed production, cob production and straw production of NK 212 feed. The results of the study showed that the highest average growth was in the K3 treatment: seed production = 9.81 (ton / ha), cob production = 6.61 (ton / ha), and straw production = 18.83 (ton / ha). It can be concluded that the application of manure can increase the production of NK 212 feed corn.